2008
DOI: 10.1177/1933719108316983
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Venous Reserve Capacity and Low Plasma Volume

Abstract: LPV decreases the capacity to cope with head-up tilt without affecting the response pattern, suggesting reduced VRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…This idea is supported by observations that, in the follicular phase, formerly PE women with subnormal plasma volume do not show elevated levels of renin-angiotensin-aldosterone system components, epinephrine or norepinephrine, compared with normal parous controls 61 . Additionally, a higher rate of presyncope under orthostatic stress in formerly PE women, and reduced venous compliance and capacitance have been observed compared with women with normal plasma volume 55,57,69 . The supposed reduced size of the venous compartment may originate from an individual's reduced fetal growth, consistent with the theory of developmental origins of adult disease, increased venous tone to compensate for conditions of increasing arterial demand, attenuated vessel reactivity or autonomic dysfunction 70 .…”
Section: Discussionmentioning
confidence: 99%
“…This idea is supported by observations that, in the follicular phase, formerly PE women with subnormal plasma volume do not show elevated levels of renin-angiotensin-aldosterone system components, epinephrine or norepinephrine, compared with normal parous controls 61 . Additionally, a higher rate of presyncope under orthostatic stress in formerly PE women, and reduced venous compliance and capacitance have been observed compared with women with normal plasma volume 55,57,69 . The supposed reduced size of the venous compartment may originate from an individual's reduced fetal growth, consistent with the theory of developmental origins of adult disease, increased venous tone to compensate for conditions of increasing arterial demand, attenuated vessel reactivity or autonomic dysfunction 70 .…”
Section: Discussionmentioning
confidence: 99%
“…preconceptual and preclinical phase of preeclampsia [18,47,48]. Low plasma volume is also associated to reduce venous reserve capacity in preeclampsia [18].…”
Section: Arterial and Venous Systemmentioning
confidence: 99%
“…Previous studies demonstrated that formerly PE women at rest have low venous reserve, characterized by low PV, low VeC, and high sympathetic tone. 10 Aerobic exercise is perhaps the best intervention to improve venous reserve. It increases PV and reduces sympathetic tone in healthy individuals.…”
mentioning
confidence: 99%